Pendidikan Karakter Pada Tari Kupu- Kupu Sebagai Falsafah Hidup Masyarakat Jawa - Sawitri Sawitri; Nurpeni Priyatiningsih; R. Adi Deswijaya; Sri Harjono (Departement of Mathematics Education, 2023)
Budaya (culture) derived from Sanskrit word “budddayah”, the plural form of word buddhi, meaning anything related to human character and mind. In English, the word culture derived from Latin word cultural. The method used was descriptive qualitative one using data obtained through in-depth interview, library study, and documentation (photograph, online magazine, research journal). Culture in the form of dance is an art product resulting from people’s creativity to fulfill material and spiritual needs. Human being has two types of needs to have balanced life. Spiritual need relates to belief and religion, while immaterial need relates to art and recreation so that life will run harmoniously. One of art forms adapting to its community is butterfly dance. Butterfly dance in its development relates to community life and art. Culture will develop and adapt to human development. Human development follows time and human need development. Butterfly dance provides human life philosophy, particularly to Javanese people. Life is gratitude, life always rotates and so does the fate. To live, an individual will need others’ help so that he should always remember Allah because life can be happy, sad, and comfortable. The one who does good deed will get goodness, and vice versa. Always respecting each other, having good mindset, and remembering death are the keys to a nice harmonious life.